Rules of international law applicable in the field of protection of the environment from pollution production and consumption waste (Journal of actual problems of jurisprudence, 2019)
This article examines some of the rules of international law applicable in the field of protection of theenvironment from pollution waste production and consumption. The global problems of our time, or, asthey say, calls, lead to the need for cooperation of all the continents of the world, including on the issue ofsolving the problems of the ecological crisis. Environmental concerns are ambitious, they go beyond theborders of a single country, and even the region. Violations of the ecological balance in nature, creating athreat to the existence of certain regions, demand for its solutions the efforts of many countries, and oftenthe entire world community.Keywords: International law, environmental protection, production, waste pollution.